Integration of Information and Communication Technology in Education: The Opportunities and Challenges - Kandel, Ganesh Kumar (Marsyangdi Journal, 2022)
This paper examines the integration of information and communication technology (ICT) in education with its challenges and opportunities. Particularly, it aims to explore how the integration of information and communication technology and tools in education have created the opportunities and challenges to teachers, students, and even to educational institutions. I reviewed books, journals and research articles to examine the integration of ICT in education, the opportunities and challenges of implementing ICT in education and some ways to mitigate these challenges. From the review of various sources, I found the growing use of ICT in education sector creating both opportunities as well as challenges. The study revealed that the integration of ICT in education has been prioritised by many countries in the world. This study also showed the necessity of integrating ICT in education system to replace the traditional pedagogy and offer relevant knowledge and skills to both students and teacher to better survive in contemporary information society. This study suggests to redesign the educational infrastructure, teacher training, curriculum structures and materials, classroom practices and modes of assessment at all levels to integrate and implement ICT in education system effectively.